2006
DOI: 10.3390/s6030208
|View full text |Cite
|
Sign up to set email alerts
|

AltiKa: a Ka-band Altimetry Payload and System for Operational Altimetry during the GMES Period

Abstract: This paper describes the Ka-band altimetry payload and system that has been studied for several years by CNES, ALCATEL SPACE and some science laboratories. Altimetry is one of the major elements of the ocean observing system to be made sustainable through the GEOSS (Global Earth Observation System of Systems) and GMES (Global Monitoring of the Environment and Security) programs. A short review of some mission objectives to be fulfilled in terms of mesoscale oceanography in the frame of the GEOSS and GMES progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 24 publications
2
40
0
Order By: Relevance
“…From Ku-to Ka-band, the scattering coefficient consequently increases by a factor 55. This leads to a penetration depth over snow surface between 0.1 m and 0.3 m in Ka-band [36]. Analysis performed on the altimeter signal acquired in Ku-and Ka-bands over the Antarctic ice sheet are consistent with this assumption.…”
Section: Complementarity Between Ku and Ka Measurements Over Ice Sheesupporting
confidence: 61%
See 1 more Smart Citation
“…From Ku-to Ka-band, the scattering coefficient consequently increases by a factor 55. This leads to a penetration depth over snow surface between 0.1 m and 0.3 m in Ka-band [36]. Analysis performed on the altimeter signal acquired in Ku-and Ka-bands over the Antarctic ice sheet are consistent with this assumption.…”
Section: Complementarity Between Ku and Ka Measurements Over Ice Sheesupporting
confidence: 61%
“…Vincent et al [36] demonstrated the feasibility of such an altimeter but also importantly the need of higher resolution altimetry to address one of the most problematic features of ocean circulation, the mesoscale eddies and fronts. These features are essential to understanding the dynamics of ocean circulation on all space and time scales and theoretical studies of the cascade of energy over scales from 100-1000 km have always suffered from the lack of high-resolution observations.…”
Section: Discussionmentioning
confidence: 99%
“…Everywhere else, the elevations from SARAL/AltiKa are 0 to 0.5 m, higher than those of ENVISAT. This pattern confirms that the penetration depth in the Ka-band is lower than in the Ku-band [31]. However, because SARAL/AltiKa and ENVISAT have a different frequency, gain pattern, and crossover points in radar altimetry, the polarization of the antenna is a problem [33].…”
Section: Saral/altika the First Preliminary Resultssupporting
confidence: 56%
“…Moreover, the Ka bandwidth is 480 MHz instead of 320 MHz; thus, the leading edge will be better sampled. In addition, we benefit from less penetration into the snowpack; theoretical calculations estimate less than one meter of penetration depth instead of 5 to 10 m in the Ku-band [31]. For the first time ever, AltiKa observes the surfaces at nadir in a simultaneously active/passive manner.…”
Section: Saral/altika the First Preliminary Resultsmentioning
confidence: 99%
See 1 more Smart Citation